1999
DOI: 10.1002/(sici)1099-1611(199905/06)8:3<237::aid-pon375>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of bereavement outcome for family carers of cancer patients

Abstract: Aims: The psychological outcome of family carers after bereavement is an important issue in evaluating palliative care services. Palliative care services have the potential to provide preventive psychosocial intervention to family carers prior to bereavement, but are faced with the need to identify those who may have greatest risk of adverse outcome. This prospective study examines predictors of psychological outcome for family carers of cancer patients following bereavement based on factors identified at ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 46 publications
7
97
1
3
Order By: Relevance
“…[28][29][30][31][32][33][34][35] The finding that a large proportion of caregivers suffered from both anxiety and depression suggests that there are unmet needs that are measurable at an early stage of the patient's life-limiting illness, and points to the need for early psychological assessment and potential intervention. 36 Our research with a subset of these same caregivers during their bereavement suggests that they are so focused on their caregiving role that their own medical needs go unattended, 37 as has been found in other studies. 38 Our findings indicate that, although patient's physical and emotional factors predict caregiver distress, perceived burden is the strongest predictor of caregiver anxiety and depression.…”
Section: Discussionsupporting
confidence: 60%
“…[28][29][30][31][32][33][34][35] The finding that a large proportion of caregivers suffered from both anxiety and depression suggests that there are unmet needs that are measurable at an early stage of the patient's life-limiting illness, and points to the need for early psychological assessment and potential intervention. 36 Our research with a subset of these same caregivers during their bereavement suggests that they are so focused on their caregiving role that their own medical needs go unattended, 37 as has been found in other studies. 38 Our findings indicate that, although patient's physical and emotional factors predict caregiver distress, perceived burden is the strongest predictor of caregiver anxiety and depression.…”
Section: Discussionsupporting
confidence: 60%
“…Several previous studies give indirect support for our findings. It has been reported that the well-being of cancer patients and their family caregivers is interrelated during the illness (Cassileth et al, 1985;Kurz et al, 1995;Kristjanson et al, 1996;Hodgson et al, 1997) and others have found the mental condition of the well partner during the terminal period to be the main risk factor of morbidity in widowhood (Kelly et al, 1999). We have no indication of that validity problems explain our findings.…”
Section: Discussioncontrasting
confidence: 50%
“…Second, the effect of family caregiving on post-death adjustment tends to be assessed qualitatively, cross-sectionally and/or retrospectively 29,[31][32][33] or over a very short period of time, 34,35 or with just two data collection points. 32,34,35 Third, there are several longitudinal studies without adequate comparison groups 28,36 whereby participants are compared to a noncaregiving sample matched to key demographics such as age, sex, domestic arrangements, and household income.…”
Section: Limitations To Current Understandings Of Caring and Bereavementmentioning
confidence: 99%
“…32,34,35 Third, there are several longitudinal studies without adequate comparison groups 28,36 whereby participants are compared to a noncaregiving sample matched to key demographics such as age, sex, domestic arrangements, and household income. These limitations exist across studies of caregivers of patients with a variety of chronic illnesses.…”
Section: Limitations To Current Understandings Of Caring and Bereavementmentioning
confidence: 99%